2016
DOI: 10.1111/dme.13078
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen activity of the serum in adolescents with Type 1 diabetes

Abstract: Adolescents with Type 1 diabetes had lower levels of serum oestrogenic activity, and these were lower than expected based on their serum oestradiol levels. We postulate that changes in the serum milieu of oestrogens in patients with Type 1 diabetes may explain their decreased oestrogenic activity and may play a role in their adverse metabolic profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 32 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…They found lower levels of estradiol and estrogenic activity in women with type 1 diabetes than controls. [22] In women with type 1 diabetes and amenorrhea there is a picture of hypothalamic hypogonadism with low FSH, LH, and estradiol [23], [24] and in our cohort of premenopausal women with type 1 diabetes, we previously reported a high prevalence of irregular menses correlating to higher CAC levels. [8], [25] Some animal models have shown estrogen to protect against hyperglycemia via decreasing HGP and increasing skeletal muscle uptake of glucose.…”
Section: 1 Discussionmentioning
confidence: 80%
“…They found lower levels of estradiol and estrogenic activity in women with type 1 diabetes than controls. [22] In women with type 1 diabetes and amenorrhea there is a picture of hypothalamic hypogonadism with low FSH, LH, and estradiol [23], [24] and in our cohort of premenopausal women with type 1 diabetes, we previously reported a high prevalence of irregular menses correlating to higher CAC levels. [8], [25] Some animal models have shown estrogen to protect against hyperglycemia via decreasing HGP and increasing skeletal muscle uptake of glucose.…”
Section: 1 Discussionmentioning
confidence: 80%
“…Data were usually expressed as E2 equivalent quantity (EEQ), which is the total concentration of estrogenic active compounds normalised to the E2. However, Martínez et al (2016) presented the results as estrogenic activity in comparison with a standard serum pool. In this study, each serum sample was tested with 0.5% serum pool, which was used as a reference standard to normalize the results.…”
Section: Estrogenic Activity As Estrogen Quantification and Biomarker Of Estrogenic Status: Methodologiesmentioning
confidence: 99%
“…Wilson et al (2003) compared the serum E2 levels in prepubertal girls affected by Turner's syndrome with healthy prepubertal girls, and found that girls with Turner's syndrome had significantly lower E2 levels. Martínez et al (2016) compared the serum estrogenic activity of post-menarcheal girls with type 1 diabetes to the estrogenic activity of normal post-menarcheal girls, finding a statistically significant difference in the estrogenic activity of girls with type 1 diabetes compared to the control group. In these two studies, the application of estrogenic activity assay allowed to demonstrate that the lack of normal ovarian function in girls with Turner's syndrome is evident even before puberty, and that type 1 diabetes can also affect estrogen metabolism.…”
Section: Female Precocious Pubertymentioning
confidence: 99%
“…This suggests that female gonadal hormones transiently protect against T1D. Consistent with this possibility, serum levels of estradiol (E2), the main estrogen, and serum estrogenic activity are decreased in adolescents with T1D, suggesting that they are not protected by E2 [19]. In addition, E2 has been shown to protect rodent and human islet survival from multiple metabolic and pro-inflammatory injuries in vivo [20, 21].…”
Section: Gender Difference In Type 1 Diabetesmentioning
confidence: 99%